Menstrual Cycle and Length of Menstruation in Early Adolescent Girls on the Incidence of Anemia - Rahman, Nur Indah Noviyanti; Johan, Reza Bintangdari; Aspar, Hukmiyah; Ernawati, Ernawati; Ruqaiyah, Ruqaiyah (Poltekkes Kemenkes Palu, 2025)
Introduction: Anemia is a prevalent health issue among adolescent girls, particularly in developing countries. This study aimed to investigate the relationship between menstrual cycle and length of menstruation on the incidence of anemia in early adolescent girls. Methods: A cross-sectional analytical survey was conducted involving 38 girls aged 12-15 years, selected using purposive sampling. Questionnaires were used to collect data on menstrual cycle and length of menstruation, while hemoglobin levels were measured to determine anemia status. Results: The results showed that 73.7% of respondents had normal menstrual cycles (21-35 days), 76.3% had normal menstrual periods (2-7 days), and 68.4% were not anemic. A significant relationship was found between menstrual cycle and anemia incidence, with 6 girls experiencing anemia despite normal cycles and 6 girls with abnormal cycles being anemic. However, no significant association was observed between length of menstruation and anemia. Conclusion: Early adolescence is a critical transition period during which health behaviors begin to develop. Adolescent girls are vulnerable to anemia due to increased iron requirements during menstruation. Efforts to prevent anemia in this population include iron and folic acid supplementation programs, minimizing risk factors, and addressing the etiology of anemia. Multisectoral support, including collaboration between health services, schools, and parents, is crucial in preventing anemia among adolescent girls. Further research with a larger, more representative sample is needed to better understand the factors contributing to anemia in this population.